Features of Decision-Making in the Process of lending to small businesses: the bDi Model and trust indices - N. E. Egorova (Финансы: теория и практика, 2022)
The aim of the study is to identify the problems hindering the effective interaction of banks with SMEs and to determine the role of trust and other institutional factors in decision-making. Despite the recovery in the SME lending sector in 2019–2020, the needs of small firms in loans are not fully satisfied. The task of enhancing interactions between banks and the sectors under study requires a fundamental approach and is relevant.The BDI (Belief-DesireIntention) model developed by M. Bratman was used as a method for investigating the decision-making process in the subject area under consideration. The place of this tool in the system of methods of analysis and support of decisionmaking processes is shown; the universality of the BDI model is substantiated and the main areas of its application are indicated.The scientific novelty of the paper is the modification of the BDI model, which is carried out by taking into account the trust factor and increasing the number of decision-making phases.The prospects of using the modified BDI model as a methodological basis for the formation of the architecture of banking ecosystems are considered. On the example of the experience of a quantitative assessment of the trust factor between banks and small firms, the possibilities of using the index method to measure other institutional factors of the modified M. Bratman model and determine the level of feasibility of a transaction planned in the area of lending are investigated.The author concluded that a necessary condition for enhancing the lending activities of banks interacting with small firms is the formation of an adequate institutional environment in accordance with the methodological principles outlined in this article.